1996
DOI: 10.1182/blood.v88.1.174.bloodjournal881174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of verocytotoxin-1 on nonadherent human monocytes: binding characteristics, protein synthesis, and induction of cytokine release

Abstract: The epidemic form of the hemolytic uremic syndrome (HUS) has been associated with a verocytotoxin producing Escherichia coli infection. Endothelial cell damage of glomeruli and arterioles of the kidney plays a central role in the pathogenesis of HUS. A number of observations in vivo and in vitro indicate that inflammatory mediators contribute to this process. In this study we investigated the binding of 125I- verocytotoxin-1 (VT-1) to freshly isolated human nonadherent monocytes as well as the nature of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Alternatively, Stx appears to be routed into a degradative pathway in both macrophages and dendritic cells of human origin [25]. Associated with this pathway, Stx induces the expression of cytokines, such as IL-1β, IL-6, IL-8, and TNF-α in human monocytes [8,26] and murine peritoneal macrophages [27] in vitro. In contrast to primary cells, a human myeloid leukemia cell line, THP-1 cells, expresses abundant Gb3 on the cell membrane and is susceptible to apoptosis by Stx through the activation of caspases 2, 6, 8, and 9 [25].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…Alternatively, Stx appears to be routed into a degradative pathway in both macrophages and dendritic cells of human origin [25]. Associated with this pathway, Stx induces the expression of cytokines, such as IL-1β, IL-6, IL-8, and TNF-α in human monocytes [8,26] and murine peritoneal macrophages [27] in vitro. In contrast to primary cells, a human myeloid leukemia cell line, THP-1 cells, expresses abundant Gb3 on the cell membrane and is susceptible to apoptosis by Stx through the activation of caspases 2, 6, 8, and 9 [25].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…In vitro studies revealed that stx can bind to human erythrocytes (15), platelets (41), and activated monocytes (160). Recent studies have found that stx immediately and more efficiently binds to polymorphonuclear leukocytes (PMNL).…”
Section: Pathogenesismentioning
confidence: 99%
“…Although Louise et al suggested that Stx may enhance the procoagulant effect of LPS [62], in vivo studies have demonstrated that toxicity of Stx is potentiated by LPS [63][64][65]. In particular, LPS, chemokines and cytokines released by inflammatory cells or injured cells upregulate the expression of Stx receptors and sensitize microvascular endothelial cells (glomerular and others) to Stx-induced injury [17,[66][67][68].…”
Section: Reviewmentioning
confidence: 99%